If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-102=6(-3x+-2)
We move all terms to the left:
-102-(6(-3x+-2))=0
We add all the numbers together, and all the variables
-(6(-3x-2))-102=0
We calculate terms in parentheses: -(6(-3x-2)), so:We get rid of parentheses
6(-3x-2)
We multiply parentheses
-18x-12
Back to the equation:
-(-18x-12)
18x+12-102=0
We add all the numbers together, and all the variables
18x-90=0
We move all terms containing x to the left, all other terms to the right
18x=90
x=90/18
x=5
| x^2=144/36 | | 70-5x=-185 | | 5x18=3x-5 | | 3(3x+4)-(2(5+2x)=42 | | (2/3)-4x+(7/2)=-9x+(5/6) | | 0.4x+1.2=-0.4 | | 98=-7(-7+n) | | 5(w-2)=-2(1.5w=5) | | 4x+16x-5=5(4x+2) | | 70-5x=185 | | 2(5x+3)-6=40 | | 8+2x-12=x+6 | | 5x+15-8x=-6 | | (10)x=(10000) | | 0.75(8x-4)=5x+2 | | 2(p-5)=4p+6 | | -9z-4=-6(z+2) | | -8+12x=-12+11x | | 5x+15-8x=-21 | | 4x(x=-3)-7x | | 2x+x-1/4=-x+3-x/2 | | 5(n+3)+6n=-2-11 | | 3x+1=2x+20 | | 4c+3(c−2)=−34 | | 8x+2=8x-7 | | (2/3)–4x+(7/2)=–9x+(5/6) | | -22+5v=6v-10 | | -4(3x-3)=1/2(-16x-8) | | 5w+15=14-3w+3 | | 7−5∣8+2x∣=-23 | | -1.1=4.4y-4.2y-0.7 | | 6+y=50 |